An enzyme-free monosaccharide fuel cell using bio-mimetically hemin-intercalated polydopamine as anode and cathode catalysts. (10th February 2022) - Lin, Weiliang; He, Minyi; Gao, Linfeng; Zhong, Haiyin; Ye, Shao; Li, Hong
Highlights: Hemin-bound polydopamine film is assembled by layer-by-layer co-deposition. H-PDA show outstanding electrocatalysis to selective oxidation of monosaccharides. H-PDA exhibit synergistically enhanced electrocatalysis to oxygen reduction. Enzyme-free glucose fuel cell is bio-mimetically designed in neutral media. H-PDA, AA and NADH can remarkably improve oxidation of glucose by oxygen. Abstract: A hemin-intercalated 5, 6-indolequinone-containing polydopamine hybrid (H-PDA) is co-assembled onto carbon-based electrodes by layer-by-layer electrodeposition methods for monosaccharide fuel cells with neutral aqueous electrolytes bio-inspired by quinohemoproteins. Hemin can promote dopamine (DA) electro-polymerization to achieve H-PDA that show synergistically enhanced electrocatalysis to the oxidation of three monosaccharides by oxygen upon incorporation of ascorbate (AA) or nicotinamide adenine dinucleotide (NADH). The electrocatalytic oxidation rate of glucose (Glc) on H-PDA is larger than that of mannose (Man) and galactose (Gal) ascribed to bi-dentate interactions of diol units at C2 /C3 (Man) or C3 /C4 (Gal) sites with PDA. On the other hand, the modification of H-PDA onto carbon nanotubes can increase largely the oxygen reduction rate and make the onset potential shifted positively, representing oxygen reduction reactions enhanced by non-enzyme and non-precious metal electrocatalysts. The simultaneous use of H-PDA as anode and cathode catalysts can improve remarkably single-compartment or two-compartment glucose fuel cell performance, leading to a 4.3-fold or 13.0-fold increase in the maximum power density. This study provides new insights into the selective oxidation of monosaccharides by oxygen in fuel cell under approximately neutral conditions using bio-mimetic electrocatalysts. Graphical abstract: Image, graphical abstract